2005
DOI: 10.1152/ajplung.00318.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the aryl hydrocarbon receptor increases pulmonary neutrophilia and diminishes host resistance to influenza A virus

Abstract: Unlike their role in bacterial infection, less is known about the role of neutrophils during pulmonary viral infection. Exposure to pollutant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD, dioxin) results in excess neutrophils in the lungs of mice infected with influenza A virus. TCDD is the most potent agonist for the aryl hydrocarbon receptor (AhR), and exposure to AhR ligands has been correlated with exacerbated inflammatory lung diseases. However, knowledge of the effects of AhR agonists on neutrophils is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 88 publications
4
86
1
Order By: Relevance
“…Concomitant with the activation of the adaptive immune responses, leukocytes are recruited to the lung and numerous soluble mediators, such as surfactant proteins, cytokines, and chemokines, are produced by infiltrating immune cells and structural cells of the lung (22)(23)(24)(25). Together, they help diminish viral replication, destroy infected cells, and promote tissue repair.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with the activation of the adaptive immune responses, leukocytes are recruited to the lung and numerous soluble mediators, such as surfactant proteins, cytokines, and chemokines, are produced by infiltrating immune cells and structural cells of the lung (22)(23)(24)(25). Together, they help diminish viral replication, destroy infected cells, and promote tissue repair.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…and tumor necrosis factor-a. These cytokines and chemokines were chosen because they stimulate leukocyte recruitment and are known to be induced during influenza A virus infection (22,26,27). In room air-exposed mice, MCP-1 levels increased within 24 hours of infection and became significantly elevated on Day 3 before declining to naive levels by Day 9 ( Figure 6A).…”
Section: Neonatal Hyperoxia Augments Pulmonary Monocyte Chemotactic Pmentioning
confidence: 99%
“…Female B6.AhR tm1Bra (AhR Ϫ/Ϫ ) mice were obtained by breeding AhR Ϫ/ϩ females with AhR Ϫ/Ϫ males. AhR Ϫ/Ϫ mice were bred at Washington State University and genotyped by PCR, as described previously (31). All mice were housed in microisolator cages in a specified pathogen-free facility at either Washington State University or the Trudeau Institute, and were provided food and water ad libitum.…”
Section: Mice Tcdd Treatment Viruses and Infectionmentioning
confidence: 99%
“…We have investigated the mechanisms underlying the immunosuppressive effects of TCDD, and have shown previously that exposure of mice to TCDD impairs multiple facets of the immune response to influenza A virus, resulting in suppressed virus-specific IgG levels, enhanced pulmonary inflammation, and altered cytokine production in the lung and draining lymph nodes (25,30,31). Importantly, we have found that during primary infection, exposure to a single dose of TCDD suppresses the proliferation of CD8 ϩ T cells in the mediastinal lymph nodes (MLN), reduces their production of IFN-␥, and impairs the generation of CTL (25,30).…”
mentioning
confidence: 99%
“…56 AhR is expressed in bone marrowderived cells such as T-and B-lymphocytes, neutrophils, and macrophages, and findings generated using AhR-deficient mice indicate that the immunomodulatory effects of dioxin are AhR-mediated. [57][58][59] Exposure to dioxin leads to profound suppression of both humoral and cellular immune responses. 60 Dioxin-activated AhR suppresses T-cells, which are its primary targets, and mediates B-cell antibody response inhibition [61][62][63] and thymic involution, with consequent thymocyte loss, premature migration of T-cell progenitors, [64][65][66] and overexpression of FAS-L in thymic stromal cells, resulting in Tcell apoptosis induction.…”
Section: Mechanisms Of Tumor Immune Escapementioning
confidence: 99%